PERCUTANEOUS EPIDURAL NEUROPLASTY (PEN) USING COMBINATION OF HYALURONIDASE AND HYPERTONIC SALINE (NaCl 3%) IN TREATING FAILED BACK SURGERY SYNDROME - Wawan Mulyawan; Yudi Yuwono Wiwoho; Syaiful Ichwan (Neurologico Spinale Medico Chirurgico, 2018)
Background: Following surgical treatments for low back pain, lower extremity pain or neurologic symptoms would last or recur, this is defined as failed sack surgery syndrome (FBSS). FBSS usually occurs in 5-40% of these surgical patients. The most common cause is an epidural scar adhesion. Percutaneous epidural neuroplasty is the non-mechanical treatment for this condition. Previously, the use of hyaluronidase and hypertonic saline separately is commonly used for epidurolysis but the combination of hyaluronidase and hypertonic saline 3% has not been explored.Objective: To investigate the two-year outcomes of percutaneous epidural neuroplasty using a combination of hyaluronidase and hypertonic saline 3% in patients with FBSS.Methods: Twelve patients who experience low back pain, with or without radiculopathy, who have underwent lumbar spine surgery previously were assigned to the study. Parameters, such as the visual analogue scale scores for the back (VAS-B) and legs (VAS-L), and the Oswestry disability index (ODI), were recorded and compared between pretreatment, 1 week, 1 month, 3 months, 1 year and 2 years follow-up.Results: For all 12 patients, the postoperative VAS-B, VAS-L, and ODI were significantly different from the preoperative values in all follow-up periods: 1 month, 3 months, 1 year, and 2 years.Conclusion: Based off this study group, percutaneous epidural neuroplasty using a combination of hyaluronidase and hypertonic saline 3% has a favourable outcome in the 2 years follow-up